Violence as an instrument in reducing women's bargaining power in the Philippines : a family economics approach - BACANI, JESSALAINE (Archīum Ateneo, 2018)
This paper analyzes the dynamics of the relationship between spousal violence and women's bargaining power, as measured by womens participation in independent decision-making in the household. In particular, it identifies whether the occurrence of spousal violence faced by women reduces their decision-making power in the household. This study uses Eswaran and Malhotras (2011) non-cooperative model of domestic violence as a theoretical framework. It employs the method of two-stage least squares (2SLS) for a simultaneous equations model (SEM) to empirically support the studys hypothesis and account for the simultaneity bias present in the model. Using data from the Philippine National Demographic Health Survey 2013 (NDHS 2013), this study finds that the occurrence of spousal violence reduces the wifes probability in having the final say in decisions involving household purchases, her own healthcare, or visits to relatives. Five control variables are also observed to significantly influence womens decision-making power. Having Islam as a religion, and age at first cohabitation are negatively related with the dependent variable, while residing in an urban area, the wife's current age and in-law support posted positive signs. The findings of this study support the improvement of the implementation of laws on domestic violence, rape, and sexual abuse to enhance women's bargaining power.